2017
DOI: 10.33736/ijbs.523.2016
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Corporate Bond Yield: The Case of Malaysian Bond Market

Abstract: Default risk has been recognized as one of the key determinants of bond yield. Past studies argue that default risk can be reflected by issue characteristics, issuer characteristics and interest rate behaviors on riskless security. As default risk is believed to be higher in developing markets due to the issue of illiquidity, capital inadequacy and a developing lending system, more empirical works must be focused on these markets. The present study examines the association between selected determinants and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 20 publications
(42 reference statements)
4
12
0
4
Order By: Relevance
“…rate coupon is one of the factors that determine the bond yield. Yahya et al (2016) found that there was a negative and significant relationship between coupon payments and bond yields. It should be noted, however, that coupon rate also reflects the amount of tax on which investors are charged considering that bonds with high coupon rates will be burdened with high taxes (Lu et al, 2010) and therefore bonds with low coupon rates will be more valuable.…”
Section: Coupon Rate and Yieldmentioning
confidence: 99%
See 4 more Smart Citations
“…rate coupon is one of the factors that determine the bond yield. Yahya et al (2016) found that there was a negative and significant relationship between coupon payments and bond yields. It should be noted, however, that coupon rate also reflects the amount of tax on which investors are charged considering that bonds with high coupon rates will be burdened with high taxes (Lu et al, 2010) and therefore bonds with low coupon rates will be more valuable.…”
Section: Coupon Rate and Yieldmentioning
confidence: 99%
“…The same conclusion results were also found by Chen et al (2007) which stated that the less illiquid of a bond will result in higher yield demand. However, Yahya et al (2016) stated that the higher volume of transactions also indicates the higher the price volatility, and consequently investors are promised to yield higher as compensation. Based on the description, it can be proposed the following hypothesis:…”
Section: Liquidity and Bond Yieldmentioning
confidence: 99%
See 3 more Smart Citations